Sediment Transport Recent Advances - Manning, Andrew J. (IntechOpen, 2022)
The effective governance and administration of many aquatic environments requires a detailed understanding of sediment transport and behavioral dynamics. This has both environmental and economic implications, especially where there is any anthropogenic involvement. Sediment Transport - Recent Advances examines sediment transport-related issues in estuarial, coastal, or freshwater environments as well as non-intrusive seismic monitoring of fluid mud, sediment removal from oil storage tanks, and formulae of sediment transport in both unsteady and steady flows.